Membranes of Polyvinylidene Fluoride and PVDF Nanocomposites with Carbon Nanotubes via Immersion Precipitation. (15th April 2008) - Mago, Gaurav; Kalyon, Dilhan M.; Fisher, Frank T.
Abstract : Microporous polyvinylidene fluoride (PVDF) and PVDF nanocomposite membranes were prepared via an isothermal immersion precipitation method using two different antisolvents (ethanol and water). The structure and morphology of the resulting membranes were investigated by wide angle X-ray diffraction (WAXD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and differential scanning calorimetry (DSC). The effects of the type of the antisolvent and the presence of multiwalled carbon nanotubes (MWNTs) on membrane morphology and the crystal structure developed within the membranes were studied. The crystallization of the PVDF upon immersion precipitation occurred predominantly in theα -phase when water is used as the antisolvent or in the absence of the carbon nanotubes. On the other hand, β -phase crystallization of the PVDF was promoted upon the use of ethanol as the antisolvent in conjunction with the incorporation of the MWNTs. The morphology and the total crystallinity of the PVDF membranes were also affected by the incorporation of the MWNTs and the antisolvent used, suggesting that the microstructure and the ultimate properties of the PVDF membranes can be engineered upon the judicious selection of crystallization conditions and the use of carbon nanotubes.